Gaya Retorika Ustadz Ashar Tamanggong dalam Ceramah Ta’ziah pada Media Youtube - Atirah, Nur; Amir, Johar; Hajrah, Hajrah (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. This study aims to describe Ustadz Ashar Tamanggong's language style in takziah lectures on YouTube media, describe Ustadz Ashar Tamanggong's voice style in takziah lectures on YouTube media and describe Ustadz Ashar Tamanggong's body gesture style in takziah lectures on YouTube media. This type of research is descriptive qualitative research. The data in this study are words, phrases, clauses and sentences that contain language styles, voice styles and body gesture styles found in Ustadz Ashar Tamanggong's ta'ziah lectures via YouTube media. The data collection technique used was the speaking technique, free of charge engagement, note-taking and documentation techniques. The data analysis technique used is the Miles and Huberman model which consists of data reduction, data presentation and conclusion. The results of this study are Ustadz Ashar Tamanggong's rhetorical style with language 1) Style based on word choice using conversational language style, informal language style, tone-based language style using simple language style, noble and powerful language style and medium language style, language style based on structure Sentences use language styles of parallelism, atthesis, epizeukis, tautotes, anaphora, and epiphora and language styles based on whether or not direct meaning use hyperbole and irony language styles. (2) Ustadz Ashar Tamanggong's voice style in the ta'ziah lecture, Ustadz Ashar Tamanggong in delivering his da'wah pays close attention to tone of voice such as pitch, pause, emphasis and speed in pronouncing words or rate. So that listeners who listen are not bored and can feel the emotions that are being built in the lecture as if the listeners feel and receive the message of da'wah in the lecture that is being delivered. (3) Ustadz Ashar Tamanggong's gesture style in the ta'ziah lecture besides using verbal language, Ustadz Ashar Tamanggong also uses nonverbal communication. Starting from how to dress neatly and politely using a blue batik shirt combined with white and maroon with a black cap, giving a smile when delivering his lecture. Move hands, fingers and eye contact as nonverbal communication to reinforce, emphasize verbal communication. Keywords: Rhetorical Style, lecture, Youtube